2022
DOI: 10.21076/vizyoner.1002922
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Health Indicators and Health Equipment of OECD Countries with the Entropy Based ARAS and SAW Methods

Abstract: Araştırmanın amacı OECD ülkelerinin, sağlık ekipmanları ve sağlık göstergeleri açısından belirlenen kriterlere göre sıralamasının yapılması ve değerlendirilmesidir. Çalışmada Çok Kriterli Karar Verme Yöntemleri tercih edilmiştir. Kriter ağırlıklarının hesaplanmasında ENTROPİ yöntemi, ülkelerin sıralamasının yapılmasında ARAS yöntemi kullanılmıştır. Araştırmada ele alınan ülkelerden eksik verileri olan ülkeler analize dahil edilmezken toplam 21 ülkenin 2018 yılına ait verileri değerlendirilmiştir. Sağlık ekipma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…SD: Standard deviation, CT: Computed tomography, MRI: Magnetic resonance imaging status indicators such as infant mortality rates and life expectancy (8,12). However, few studies have been interested in indicators of health equipment (13). In this study, we included more health equipment indicators in the dataset.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SD: Standard deviation, CT: Computed tomography, MRI: Magnetic resonance imaging status indicators such as infant mortality rates and life expectancy (8,12). However, few studies have been interested in indicators of health equipment (13). In this study, we included more health equipment indicators in the dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Nine OECD countries, namely Costa Rica, Colombia, France, Germany, Japan, the Netherlands, Portugal, Switzerland, and the United Kingdom, were excluded from the analysis because of missing data for one or more indicators. Previous authors also reported issues in data availability for some indicators and members of OECD countries (10,13,15).…”
Section: Data Setmentioning
confidence: 99%
See 1 more Smart Citation